Disponibilidad y accesibilidad en el transporte público madrile\~no como garantía de equidad social ante la aplicación de un peaje urbano para la ciudad de Madrid - Juan Pedro Mu\~noz Miguel; Clara Simón de Blas; Ana Elizabeth García Sipols (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
– A sufficiently accessible public transport, is one of the main factors for the implementation of congestion charging, which ensures addition, an adequate level of social equity in mobility, a high degree of social acceptance. This article based on a population survey for the City of Madrid and its surroundings, provides an assessment of the current transport accessibility features Madrid to guarantee social equity in low mobility urban pricing situations, where the results show as the system would ensure a level of fairness in the mobility very meaningful and relevant to interior and radial displacements respectively with very limited scope for transverse displacements, although the use of certain strategies can be a crucial factor that promotes fairness socially desirable for the congestion charge.
Keywords: R41; 330; Congestion; Public transport; Road pricing; Social equity